2008
DOI: 10.1358/mf.2008.30.1.1147769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Persea americana Mill (Lauraceae) (avocado) ethanolic leaf extract (PAE) on blood glucose and kidney function in streptozotocin (STZ)-induced diabetic rats and on kidney cell lines of the proximal (LLC-PK1) and distal tubules (MDBK)

Abstract: Extracts of Persea americana Mill (Lauraceae) ("Avocado") have been traditionally used to treat hypertension and diabetes mellitus. Accordingly, we studied the hypoglycaemic and renal function effects of P. americana leaf ethanolic extracts (PAE) in STZ-induced diabetic rats. Oral glucose tolerance responses to various doses of PAE were monitored in fasted rats following a glucose load. Rats treated with deionized water or standard hypoglycaemic drugs acted as untreated and treated positive controls, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…15 Briefly, the tissue samples (1-1.5 g) were homogenized in 2 mL of 30% KOH solution and digested at 100°C for 30 min and then cooled in ice-saturated sodium sulfate. The glycogen was precipitated with ethanol and then pelleted, washed, and resolubilized in deionized water.…”
Section: Glycogen Contentmentioning
confidence: 99%
“…15 Briefly, the tissue samples (1-1.5 g) were homogenized in 2 mL of 30% KOH solution and digested at 100°C for 30 min and then cooled in ice-saturated sodium sulfate. The glycogen was precipitated with ethanol and then pelleted, washed, and resolubilized in deionized water.…”
Section: Glycogen Contentmentioning
confidence: 99%
“…Because of the high demand for P. Americana fruit worldwide owing to its high nutritional value and reported health benefits, including anticancer activity, the food industry has grown tremendous interest in processing this crop and enhancing its value (Lu et al, 2005). P. americana leaves' extracts have been used as analgesic, anti-inflamatory, hypoglycaemic, anticonvulsant, antidiabetic and vasorelaxant among other therapeutic uses (Adeyemi et al, 2002;Antia et al, 2005;Gondwe et al, 2007;Ojewole and Amabeoku, 2006;Owolabi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies by Antia et al (2005) and Gondwe et al (2008) have shown that administration of Persea americana leaf extract may have a hypoglycaemic effect. Studies suggest that a decrease of the serum glucose level and increase glucose uptake, via the protein kinase B (PKB/Akt) pathway, could be produced by flavonoids (Cazarolli et al, 2009;Tzeng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%